Najčešće pogreške u uporabi prijedloga hrvatskoga jezika kod izvornih govornika španjolskoga jezika - Korljan Bešlić, Josipa (SlavVaria, 2024)
The most common mistakes in using prepositions in the Croatian language by native speakers of the Spanish language. Prepositions are an invariable type of word, but quite often used at the sentence level. The central question posed by this paper is what mistakes native speakers of Spanish, who are learning Croatian at beginner levels (A1 and A2), make when using Croatian prepositions, considering that Croatian and Spanish prepositions differ in usage. The mistakes were analyzed based on essay texts written in the Croatian Language for Foreigners course at the CEHAS program at the Faculty of Humanities and Social Sciences in Split. The errors were systematized according to prepositions and cases. In the final part of the paper, possibilities for eliminating and preventing this type of errors are outlined.